PENGARUH KAPUR PADA MEDIA TANAM TERHADAP PERTANAMAN CABAI MERAH - Eni Miftahul Janah; Idwar; Armaini (UIR Press, 2020)
ABSTRACT Red chili has a potential to be developed in sub-optimal land (Inceptisol, Ultisol, and peatland) by adding lime as amelioration. Besides that good characteristics of peat soils can also improve Ultisol and Inceptisol soils when is mixed. With the application of these technologies can increase the productivity of red chili. This study aimed to examine the effect of agricultural lime on several growing media and to determine the best treatment on the growth and yield of red chili. The study was conducted at the experimental farm of the Faculty of Agriculture, University of Riau from April to September 2018. The research was carried out in factorial with 2 factors and designed by completey randomized design and then tested with Duncan's new multiple range test. The first factor was media Ultisol, Inceptisol, peat, peat+Ultisol, and peat+Inceptisol. The second factor consisted of lime 0,0 x Al-dd, 1,0 x Al-dd and 2,0 x Al-dd. The observed parameters were stem diameter, flowerage, number, length, diameter, and weight. The results showed that lime application 1,0 x Al-dd for Inceptisol provided a good effect on stem diameter, flowerage, number, length, diameter, and fruit weight. The best treatment was found in 1,0 x Al-dd on peat+Inceptisol with a productivity of 135,10 per plant. Keywords: Lime, Planting media, Chili, Ultisol, Inceptisol, Peat,